1979
DOI: 10.1084/jem.149.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeterminant specificity of human immunity to type III group B streptococcus.

Abstract: The type III polysaccharides of group B Streptococcus in its native state chemically consists of glucose, galactose, glucosamine, and sialic acid. The core of this polysaccharide lacks sialic acid and precipitates with type III antiserum to give a partial identity with the precipitate between the native antigen and this serum. The core determinant is immunochemically similar to the capsular polysaccharide of type XIV Streptococcus pneumoniae, while the native type III group B streptococcal polysaccharide does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 19 publications
(35 reference statements)
3
69
1
Order By: Relevance
“…Although type III strains were not lethal in this standard animal model, type III-specific protective immunity has now been established in models for lethal infection in mice (23)(24)(25), chick embryos (9,26), and suckling rats (27 (1,3,8,9,16). This presumably "protective" antibody has specificity for the native III polysaccharide (2,5), is an IgG immunoglobulin (1,8,9), and is placentally transferred in concentrations that, beyond 35-36 wk of gestation, approach that in maternal serum (1,9). In addition, it promotes opsonophagocytosis and killing of type III strains by polymorphonuclear leukocytes in the presence of complement (4,18), is protective in animal models when sufficient concentrations are administered before or concomitant with challenge (9,25,26), and can modify the terminal sialic acid moieties of the type III capsule in a manner that permits activation of the alternative pathway (4).…”
Section: Discussionmentioning
confidence: 99%
“…Although type III strains were not lethal in this standard animal model, type III-specific protective immunity has now been established in models for lethal infection in mice (23)(24)(25), chick embryos (9,26), and suckling rats (27 (1,3,8,9,16). This presumably "protective" antibody has specificity for the native III polysaccharide (2,5), is an IgG immunoglobulin (1,8,9), and is placentally transferred in concentrations that, beyond 35-36 wk of gestation, approach that in maternal serum (1,9). In addition, it promotes opsonophagocytosis and killing of type III strains by polymorphonuclear leukocytes in the presence of complement (4,18), is protective in animal models when sufficient concentrations are administered before or concomitant with challenge (9,25,26), and can modify the terminal sialic acid moieties of the type III capsule in a manner that permits activation of the alternative pathway (4).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it would appear that the type IV polysaccharide (17) resembles more that of type Ib (7,8) in which this conformational dependence was not detected.…”
Section: Resultsmentioning
confidence: 84%
“…While still retaining type-specificity, these acid extracted antigens are structurally and, in most cases, immunologically incomplete. They form the lower molecular weight core structures of their respective native antigens, which all contain additional terminal sialic acid residues (4)(5)(6)(7)(8). The structures of the types Ia, Ib, 11, and I11 capsular polysaccharides have been elucidated (9-1 l), and the important role of sialic acid in the pathogenicity of GBS (12) Can.…”
mentioning
confidence: 99%
“…They were shown to be safe, but their immunogenicity was disappointing (3,7). These CPS, when coupled to carrier proteins such as tetanus toxoid, were shown to be more immunogenic in preclinical animal assays (15,20,24,25,(30)(31)(32) and human clinical trials (5,6,13), and as expected, the protection was shown to be type specific (3,12,13). Based on the current information on serotype distribution, a conjugate vaccine would have to include types Ia, Ib, II, III, and V to prevent the majority of disease in North America.…”
mentioning
confidence: 66%